Neuraminidase Inhibitors for Critically Ill Children With Influenza - Louie, Janice K. (Pediatrics, 2013)
OBJECTIVE: Timely treatment with neuraminidase inhibitor (NAI) drugs appears to improve survival in adults hospitalized with influenza. We analyzed California surveillance data to determine whether NAI treatment improves survival in critically ill children with influenza. METHODS: We analyzed data abstracted from medical records to characterize the outcomes of patients aged 0 to 17 years hospitalized in ICUs with laboratory-confirmed influenza from April 3, 2009, through September 30, 2012. RESULTS: Seven hundred eighty-four influenza cases aged <18 years hospitalized in ICUs had information on treatment. Ninety percent (532 of 591) of cases during the 2009 H1N1 pandemic (April 3, 2009–August 31, 2010) received NAI treatment compared with 63% (121 of 193) of cases in the postpandemic period (September 1, 2010–September 30, 2012; P < .0001). Of 653 cases NAI-treated, 38 (6%) died compared with 11 (8%) of 131 untreated cases (odds ratio = 0.67, 95% confidence interval: 0.34–1.36). In a multivariate model that included receipt of mechanical ventilation and other factors associated with disease severity, the estimated risk of death was reduced in NAI-treated cases (odds ratio 0.36, 95% confidence interval: 0.16–0.83). Treatment within 48 hours of illness onset was significantly associated with survival (P = .04). Cases with NAI treatment initiated earlier in illness were less likely to die. CONCLUSIONS: Prompt treatment with NAIs may improve survival of children critically ill with influenza. Recent decreased frequency of NAI treatment of influenza may be placing untreated critically ill children at an increased risk of death.